PROCEDURE FOR DETERMINING PRIORITY OF AREAS OPERATIONAL ACTIONS FOR THE FORCES OF THE NATIONAL GUARD OF UKRAINE UNDER AN THE STATE OF THE COUNTRY EMERGENCE SITUATION OF THE SOCIAL CHARACTER - Batsamut V. М. (Honor and Law, 2019)
Designed the procedure which allows to determine the priorities of operational areas of action, while the event in several regions of the country’s emergency social situations resulting from massive illegal actions of citizens. As part of the procedure developed system of indicators that characterize the danger of a certain emergency situation, the criterion is the order of ranking of different areas of operational activities in the extent arising from these dangers.